Analisis Pemantauan Sebaran TSS Menggunakan Aplikasi Google Earth Engine Sebagai Dasar Pengelolaan Pesisir Terpadu Di Wilayah Sekitar Pantai Pasir Padi - Farhaby, Arthur Muhammad; Guskarnali, Guskarnali; Setiawan, Fahri; Winarto, Mito; Arianto, Firdaus Dwi (Jurnal Laut Khatulistiwa, 2026)
Abstract The coastal waters surrounding Pasir Padi Beach, located on the eastern side of Pangkalpinang, constitute a transitional zone between terrestrial and marine environments that is highly susceptible to sedimentation pressure, particularly from tin mining activities. This study aims to map and analyze the distribution and concentration of Total Suspended Solids (TSS) in the coastal waters of Pasir Padi Beach and its surrounding areas. The monitoring was carried out using a Google Earth Engine–based platform over a four year period (2022–2025) utilizing Sentinel 2A satellite imagery. The analysis employed a modified version of the Parwati method to estimate TSS. The findings revealed TSS concentrations ranging from 60–80 mg/L and >80 mg/L, represented by red and orange colors, which were predominantly distributed along the coastline. Meanwhile, the green areas, indicating TSS concentrations of 20–30 mg/L, functioned as a transitional or coastal belt before reaching the offshore waters characterized by low TSS values of 0–20 mg/L, depicted in blue. These results demonstrate that regions located near river mouths and tin mining zones are more prone to high sedimentation intensity, with the highest accumulation occurring toward offshore areas. Consequently, periodic monitoring is essential to mitigate potential environmental impacts such as river mouth siltation and disruptions to coastal dynamics and coastal activities.